Preventable Hospitalizations and Emergency Department Visits for Angina, United States, 1995-2010 - Paula W. Yoon, ScD, MPH; Amy L. Valderrama, PhD, RN; Julie C. Will, PhD, MPH (Centers for Disease Control and Prevention, 2013)
Introduction Preventable hospitalizations for angina have been decreasing since the late 1980s - most likely because of changes in guidance, physician coding practices, and reimbursement. We asked whether this national decline has continued and whether preventable emergency department visits for angina show a similar decline. Methods We used National Hospital Discharge Survey data from 1995 through 2010 and National Hospital Ambulatory Medical Care Survey data from 1995 through 2009 to study preventable hospitalizations and emergency department visits, respectively. We calculated both crude and standardized rates for these visits according to technical specifications published by the Agency for Healthcare Research and Quality, which uses population estimates from the US Census Bureau as the denominator for the rates. Results Crude hospitalization rates for angina declined from 1995-1998 to 2007-2010 for men and women in all 3 age groups (18-44, 45-64, and ≥65) and age- and sex-standardized rates declined in a linear fashion (P = .02). Crude rates for preventable emergency department visits for angina declined for men and women aged 65 or older from 1995-1998 to 2007-2009. Age- and sex-standardized rates for these visits showed a linear decline (P = .05). Conclusion We extend previous research by showing that preventable hospitalization rates for angina have continued to decline beyond the time studied previously. We also show that emergency department visits for the same condition have also declined during the past 15 years. Although these declines are probably due to changes in diagnostic practices in the hospitals and emergency departments, more studies are needed to fully understand the reasons behind this phenomenon.